DIAGNOSTIC ACCURACY OF CONTRAST-ENHANCED PANCREATIC ULTRASOUND FOR DIAGNOSING NEOPLASTIC PANCREATIC LESIONS: A SYSTEMATIC REVIEW - Martupa Lumbantoruan, Johannes (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: In recent years, there has been evidence to support the utility of contrast-enhanced ultrasound (CEUS) as a minimally invasive diagnostic technique for diagnosis of pancreatic neoplasms.Objective: To assess the diagnostic accuracy of CEUS in distinguishing between benign and malignant pancreatic neoplasms.Methods: A systematic review of literature published between 2012 and August 2023 was performed across several databases including PubMed, Cochrane Library, ProQuest, and Google Scholar.Results: A total of 8 studies investigating the diagnostic utility of CEUS for benign and malignant pancreatic neoplasms were eligible for inclusion in this review. These studies included a total of 641 patients who participated in five prospective studies and three retrospective studies. Four studies included patients of Caucasian descent, while the remaining four studies included patients of Asian descent. In seven studies, 2,4 ml of Sonovue was used as the contrast agent, while in one study, 2.5 g of Levovist was used. CEUS has a sensitivity which ranges from 73.7% to 100% and specificity which ranges from 61.7%% to 97.2%, and excellent accuracy for the qualitative diagnosis of benign and malignant pancreatic neoplasms.Conclusion: CEUS has good sensitivity, specificity, and accuracy for the qualitative diagnosis of benign and malignant pancreatic neoplasms. These data demonstrate that CEUS is an important imaging tool for characterization of pancreatic tumours and is extremely successful for the diagnosis of benign and malignant pancreatic neoplasms.